Upregulation of p53 by tannic acid treatment suppresses the proliferation of human colorectal carcinoma - Karakurt Serdar; Kandir Sinan; Gökçek-Saraç Çiğdem (Acta Pharmaceutica)
The present study’s objective is to clarify the molecular mechanisms of tannic acid effects on the viability of human colorectal carcinoma (CRC). Tannic acid is stable for up to 48 h and is localized in both cytoplasm and nucleus. It dose-dependently inhibited the viability of CRC cell lines; SW-620 and HT-29 with IC50 values of 7.2 ± 0.8 and 37.6 ± 1.4 µmol L–1. Besides, metastatic, invasive, and colony formation properties of CRC cells were significantly inhibited following the tannic acid treatment (p < 0.001). Tannic acid has been found to modulate enzyme, protein, and gene expressions of NQO1 in different levels and the upregulation of protein/gene expressions of p53 (p < 0.001), which leads the cells to trigger apoptosis. In conclusion, the present in vitro study may supply a significant background for in vivo studies in which the molecular mechanisms of antioxidant and chemopreventive activities of tannic acid will completely clarify.